B-CD8+ T Cell Interactions in the Anti-Idiotypic Response against a Self-Antibody - Darel Martínez; Amaury Pupo; Lianet Cabrera; Judith Raymond; Nichol E. Holodick; Ana María Hernández (Journal of Immunology Research)
P3 is a murine, germline, IgM mAb that recognizes N-glycolylated gangliosides and other self-antigens. This antibody is able to induce an anti-idiotypic IgG response and B-T idiotypic cascade, even in the absence of any adjuvant or carrier protein. P3 mAb immunization induces the expression of activation markers in a significant percentage of B-1a cells in vivo. Interestingly, transfer of both B-1a and B-2 to BALB/Xid mice was required to recover anti-P3 IgG response in this model. In fact, P3 mAb activated B-2 cells, in vitro, inducing secretion of IFN-γ and IL-4, although this activation was not detected ex vivo. Interestingly, naïve CD8+ T cells increased the expression of activation markers and IFN-γ secretion in the presence of B-1a cells isolated from P3 mAb-immunized mice, even without in vitro restimulation. In contrast, B-2 cells were able to stimulate CD8+ T cells only if P3 was added in vitro. Using bioinformatics, a MHC class I-binding peptide from P3 VH region was identified. P3 mAb was able to induce a specific CTL response in vivo against cells presenting this peptide. Both humoral and CTL anti-idiotypic responses could be mechanisms to protect against the self-reactive antibody, contributing to keeping the tolerance to self-antigens.